Population pharmacokinetics of subcutaneous C1‐inhibitor for prevention of attacks in patients with hereditary angioedema. Issue 10 (26th August 2018) - Pawaskar, Dipti; Tortorici, Michael A.; Zuraw, Bruce; Craig, Timothy; Cicardi, Marco; Longhurst, Hilary; Li, H. Henry; Lumry, William R.; Martinez‐Saguer, Inmaculada; Jacobs, Joshua; Bernstein, Jonathan A.; Riedl, Marc A.; et al.
Summary: Background: Long‐term prophylaxis with subcutaneous (SC) administration of a highly concentrated plasma‐derived C1‐esterase inhibitor (C1‐INH) formulation was recently approved by the Food and Drug Administration for hereditary angioedema (HAE) attack prevention. Objective: To characterize the population pharmacokinetics of C1‐INH (SC) (HAEGARDA ® ; CSL Behring) in healthy volunteers and HAE patients, and assess the variability and influence of covariates on pharmacokinetics. Methods: C1‐INH functional activity data obtained after administration of various C1‐INH (intravenous; IV) and C1‐INH (SC) doses from 1 study in healthy volunteers (n = 16) and 2 studies in subjects with HAE (n = 108) were pooled to develop a population pharmacokinetic model (NONMEM v7.2). Pharmacokinetic parameters derived from steady‐state simulations based on the final model were also evaluated. Results: C1‐INH functional activity following C1‐INH (SC) administration was described by a linear one‐compartment model with first‐order absorption and elimination, with inter‐individual variability in all parameters tested. The mean population bioavailability of C1‐INH (SC), and pharmacokinetic parameters for clearance (CL), volume of distribution, and absorption rate were estimated to be ~43%, 1.03 mL/hour/kg, 0.05 L/kg and 0.0146 hour −1, respectively. The effect of bodyweight on CL of C1‐INH functional activity was included in the final model, estimated to be 0.74. Steady‐state simulations of C1‐INH functional activity vs time profiles in 1000 virtual HAE patients revealed higher minimum functional activity ( C trough ) levels after twice‐weekly dosing with 40 IU/kg (~40%) and 60 IU/kg (~48%) compared with 1000 IU IV (~30%). Based on the population pharmacokinetic model, the median time to peak concentration was ~59 hours and the median apparent plasma half‐life was ~69 hours. Conclusions and Clinical Relevance: Twice‐weekly bodyweight‐adjusted dosing of C1‐INH (SC) exhibits linear pharmacokinetics and dose‐dependent increases in C trough levels at each dosing interval. In this analysis, SC dosing led to maintenance of higher C trough levels than IV dosing.